Feminization, rural transformation, and wheat systems in post-soviet Uzbekistan - Najjar, Dina; Devkota, Rachana; Feldman, Shelley (Elsevier, 2022)
This paper examines how rural transformation in Uzbekistan alters gender norms and roles and, consequently, affects women’s involvement in agriculture. We focus on the role that contextual factors, particularly kinship relations, government goals, and institutional structures each contribute to rural transformation and male outmigration, and how these, in turn, increase women’s work in wheat production and processing. The wheat is the most important crop in the country which has the highest area coverage (35%) in Uzbekistan. We begin by highlighting the post-Soviet transition in Uzbekistan and its effects on the agricultural sector, including how households respond to opportunities for innovation. We then move to a discussion of our methodological approach drawing on insights from the GENNOVATE project, a collaborative initiative across 11 CGIAR centres that explored the relationship between changing gender norms in relation to women’s roles in agricultural production and processing. Next, we examine an understudied topic in migration research i.e., how the transformation of agriculture contributes to increased dependence on unpaid female agricultural labour. We conclude with an analysis of how the feminization of agriculture alters household relations and women’s participation in the public sphere. Significantly, we close with a reflection on what these changes mean for gender and innovation studies.